The Application of Mind Mapping in Enhancing Students' Understanding of Fiqh on the Requirements of Qurban: A Study in Grade V at MI Jabal Nur - Pratami, Rosmala Sari Putri; Darmayanti, Darmayanti; Yahya, Safaruddin (Journal of English Language and Education, 2025)
This study aims to enhance students' understanding and performance in the Grade V Fiqh curriculum at MI Jabal Nur through the Mind Mapping teaching method. Mind Mapping is a visual learning technique that organizes information graphically, promoting better comprehension. An experimental approach was employed to assess its effectiveness in improving students’ understanding of the requirements of Qurban. Data collection involved three main instruments. First, observations were conducted using structured sheets to analyze student and teacher activities during lessons. Second, an experiment divided students into an experimental group (Mind Mapping) and a control group (conventional methods), with pre-tests and post-tests measuring learning outcomes. Third, documentation included relevant photographs. The procedure encompassed observations, experimental interventions, and assessments. Quantitative analysis was applied to evaluate student progress and teacher effectiveness. The findings revealed significant improvements. The success rate increased from 47% in the pre-cycle to 93.33% in Cycle II, with the average student score rising from 59.6 to 85.9. These improvements were attributed to enhanced teacher performance, additional learning activities, and greater student engagement. Mind Mapping effectively facilitated information visualization, fostering deeper understanding. This study demonstrates that the Mind Mapping method positively impacts students' comprehension and academic performance in Fiqh. Its structured and interactive nature helps learners better grasp complex religious concepts, making it a valuable pedagogical tool in Islamic education.